Expression profiles and characteristics of human lncRNA in normal and asthenozoospermia sperm†. Issue 4 (4th December 2018) - Zhang, Xiaoning; Zhang, Peng; Song, Dandan; Xiong, Suping; Zhang, Hongyan; Fu, Jianbo; Gao, Fengxin; Chen, Houyang; Zeng, Xuhui
Abstract: Increasing studies have shown that specific mRNAs and miRNAs expressed in mature sperm may be related to sperm motility. However, the expression profiles and roles of lncRNAs in sperm remain unknown. In the present study, numerous lncRNAs were identified in human sperm, and some lncRNAs were expressed exclusively in sperm and testis. Compared with those in normal sperm, the lncRNA expression profiles in asthenozoospermia (AZS) sperm showed significant differences. Gene ontology and pathway analyses showed that function of differentially expressed lncRNA targets and mRNAs between AZS and normal sperm were closely linked with many processes involved in spermatogenesis and sperm function. Furthermore, among the upregulated lncRNAs in AZS sperm, lnc32058, lnc09522, and lnc98487, which exhibited specific/enriched sperm and testicular expression, increased simultaneously in the same AZS sperm samples, and their expression levels were correlated with sperm progressive motility. This is the first systematic study of lncRNA expression profiles in human mature sperm indicating an association between lncRNA expression and sperm motility. The study provides a preliminary database for identifying lncRNAs crucial for human spermatogenesis and sperm function, and new insights into our understanding of the regulation of sperm motility and causes of male infertility. Abstract : Numerous lncRNAs were identified and compared between normal and asthenozoospermic patients' sperm, which showed significant differences suggesting that some key sperm/testis-specific/enriched lncRNAs play a role in sperm motility.